Low-cost Volumetric Ultrasound by Augmentation of 2D Systems: Design and Prototype. (January 2018) - Herickhoff, Carl D.; Morgan, Matthew R.; Broder, Joshua S.; Dahl, Jeremy J.
Conventional two-dimensional (2D) ultrasound imaging is a powerful diagnostic tool in the hands of an experienced user, yet 2D ultrasound remains clinically underutilized and inherently incomplete, with output being very operator dependent. Volumetric ultrasound systems can more fully capture a three-dimensional (3D) region of interest, but current 3D systems require specialized transducers, are prohibitively expensive for many clinical departments, and do not register image orientation with respect to the patient; these systems are designed to provide improved workflow rather than operator independence. This work investigates whether it is possible to add volumetric 3D imaging capability to existing 2D ultrasound systems at minimal cost, providing a practical means of reducing operator dependence in ultrasound. In this paper, we present a low-cost method to make 2D ultrasound systems capable of quality volumetric image acquisition: we present the general system design and image acquisition method, including the use of a probe-mounted orientation sensor, a simple probe fixture prototype, and an offline volume reconstruction technique. We demonstrate initial results of the method, implemented using a Verasonics Vantage research scanner.